Crisis dead – long live the crisis! Apple inc.: managing the post-pandemic and cargo thefts crises - Ahsan, Jaweria; Šilenskytė, Aušrinė (Routledge, 2023)
Supply chain thefts have caused a crisis for companies in various industries multiple times. Thefts had been partially put on hold because of COVID-19, but companies should be ready to face the emergency when the lockdown eases. This case describes the challenges faced by Apple’s international logistics manager, who needed to design preventative actions for the constantly repeating crisis caused by the theft of Apple’s iPhone shipments and to ensure that the expected emergency in the post-COVID era would not hit the company. The case helps stimulate classroom/group discussions on all three phases (the pre-crisis, the crisis, and the post-crisis) of global crisis management. When solving the case, students are encouraged to apply holistic thinking for crisis assessment and management, and to evaluate the benefits of industry stakeholder collaboration and the role of technological innovations in long-term crisis prevention. The case offers a teaching plan that comprises two levels of complexity and can be used for undergraduate, MBA, or MSc-level studies.
Keywords: global smartphone industry; cargo thefts; crisis assessment and prevention; blockchain; fi=Strateginen johtaminen|en=Strategic Management|